Konsep Pendidikan Karakter Dalam Buku Membangun Moral Bangsa Melalui Akhlak Tasawuf Karya Muhammad Iqbal Irham - Suparno; Lisa Ariska Prayitno (Jurnal Pendidikan Agama Islam Miazhar, 2025)
This study explains the analysis of the role of kyai in the formation of the discipline character of students, The character of students is a behavior that students have since birth, but for the discipline character of students this grows starting from the education of parents or guardians of previous students who then continue the education to Islamic boarding schools where the education of the students will be guided directly by kyai and assisted by the ustadz-ustadzah in the Mambaus Sholihin Roudlotul Muta'allimin Islamic boarding school, Suci Village, Manyar District, Gresik. While in the education of kyai and these ustadz-ustadzah there will be a good change again in the discipline character of these students, where the character that is not good or not yet disciplined will gradually change over time in studying at the Islamic boarding school. This type of research is descriptive qualitative research by selecting students at the Mambaus Sholihin Roudlotul Muta'allimin Islamic Boarding School, Suci Village, Manyar District, Gresik as a sample and three informants who are considered to have knowledge and information regarding the problem being studied, namely the Role of Kyai in the Formation of Disciplined Character of Students at the Mambaus Sholihin Roudhotul Muta'allimin Islamic Boarding School, Suci Village, Manyar District, Gresik Regency. Data collection techniques used are observation, interviews, and documentation. To check the validity of the data in this study using a credibility test. The results of this study show quite good results related to the Role of Kyai in the Formation of Disciplined Character of Students at the Mambaus Sholihin Roudlotul Muta'allimin Islamic Boarding School by interviewing informants seen from the interview indicators, namely the role of kyai in the formation of disciplined character of students and the disciplined character of students at the Mambaus Sholihin Roudlotul Muta'allimin Islamic Boarding School, Suci Village, Manyar District, Gresik Regency.